A non-enzymatic disposable electrochemical sensor based on surface-modified screen-printed electrode CuO-IL/rGO nanocomposite for a single-step determination of glucose in human urine and electrolyte drinks. Issue 25 (11th June 2021) - Janmee, Nopparat; Preechakasedkit, Pattarachaya; Rodthongkum, Nadnudda; Chailapakul, Orawon; Potiyaraj, Pranut; Ruecha, Nipapan
Abstract : A novel designed device of CuO-IL/rGO-modified SPCE combined with NaOH-coated wax-printed paper was developed as a non-enzymatic glucose sensor with single-step sample loading in human urine and electrolyte drinks via portable potentiostat. Abstract : A non-enzymatic disposable electrochemical sensor coupled with an automated sample pretreatment paper-based device was developed to avoid an additional sample preparation step for glucose determination in human urine and electrolyte drinks. The automated sample pretreatment paper-based device was successfully fabricated by the simple coating of a strong alkaline solution on a patterned wax paper, and then attached on an electrochemical sensor. The nanocomposite of copper oxide nanoparticles, ionic liquid and reduced graphene oxide (CuO-IL/rGO) modified on the screen-printed carbon electrode (SPCE) was created and used as a non-enzymatic electrochemical glucose sensor. The presence of the CuO-IL/rGO nanocomposite on the screen-printed electrode surface was confirmed by transmission electron microscopy (TEM), scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction spectroscopy (XRD). Under optimal conditions, glucose was measured by dropping 100 μL sample solution on the device and detected via chronoamperometry (CA) using a smartphone potentiostat controlled by Android app., providing a rapid current response within 20 s and linearity in a range of 0.03–7.0 mM with a limit of detection (LOD) of 0.14 μM. Furthermore, this developed device was successfully applied for determining glucose levels in human urine and electrolyte drinks, exporting satisfying results correlated with a commercial enzymatic glucose biosensor and labeled values of the commercial products. Therefore, this device could be an alternative device for a non-enzymatic glucose sensor with single-step sample loading, allowing for real-time analysis, low cost, portability, disposability, and on-field measurement.